Data Sheet 3_Fostering interdisciplinary cancer research education: collaboration networks, publication outcomes, and participant experiences from an inaugural Research Day.docx - Okunsogie Jessica Osaze (22679363) (2025)
Background Interdisciplinary collaboration is increasingly recognized as essential for advancing cancer research, yet institutional mechanisms fostering such networks are rarely systematically evaluated. Objective We analyzed the inaugural 2023 Ellis Fischel Cancer Center (EFCC) Research Day to characterize collaboration patterns, research themes, publication outcomes, and participant experiences across four thematic program areas. Methods We employed a convergent parallel mixed methods design, integrating quantitative analysis of 78 research abstracts with qualitative semi-structured interviews of seven participants. Abstracts were categorized across Cancer Prevention, Control, Outreach and Engagement Program (CPCOEP), Theranostics and Molecular Imaging Program (TMIP), Immunomodulation and Regenerative Medicine Program (IRMP), and Comparative Oncology and Translational Medicine Program (COTMP). Publication outcomes were tracked through systematic database searches over 22 months. Event attendance (n = 203) was documented through registration records. Interviews conducted September–October 2025 explored collaboration experiences and event value. Results Abstract distribution showed CPCOEP (13, 17%), TMIP (26, 33%), IRMP (28, 36%), and COTMP (11, 14%). Teams averaged 5.47 co-authors and 2.54 collaborating institutions. Graduate students comprised 32% of first authors. Within 22 months, 11.5% of abstracts yielded peer-reviewed publications, 10.3% conference abstracts, while 75.6% remained unpublished. Attendance analysis revealed 203 participants: faculty (32.0%), graduate students (18.2%), research staff (13.8%), undergraduates (12.8%), and postdoctoral researchers (11.3%). Qualitative interviews demonstrated that four of seven participants formed new research partnerships, with a collaborative grant submission resulting. Participants valued poster sessions for substantive one-on-one discussions but identified structural barriers including poster placement, limited dedicated networking time, and challenges balancing presentation duties with exploring others' research. Conclusions Structured institutional research events successfully engage researchers across career stages and foster measurable interdisciplinary collaborations. However, intentional design elements including thematic networking sessions, dedicated collaboration time, and career development programming could enhance translational impact.